2001
DOI: 10.1021/ac011018a
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Tocopherol Isomers Using Capillary Electrochromatography:  Comparison of Monomeric and Polymeric C30 Stationary Phases

Abstract: The comparison of tocopherol isomer separation achieved using different stationary-phase alkyl chain lengths (i.e., C18 vs C30) and modes of alkyl phase attachment to the silica-based supports (i.e., polymeric vs monomeric synthesis) using capillary electrochromatography (CEC) has been demonstrated. The smaller alkyl chain does not exhibit the shape selectivity needed to resolve all of the tocopherol isomers. Conversely, both polymeric and monomeric C30 phases show increased tocopherol isomer selectivity. Chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Using CEC, compounds with closely similar properties can be resolved in a short time with minimal solvent consumption. The separation of vitamin E components by CEC using packed columns has been described [20][21][22][23][24][25]. Quantitation studies of these compounds in edible oils with a CEC-packed column have been reported [24], but application to detect oil adulteration was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Using CEC, compounds with closely similar properties can be resolved in a short time with minimal solvent consumption. The separation of vitamin E components by CEC using packed columns has been described [20][21][22][23][24][25]. Quantitation studies of these compounds in edible oils with a CEC-packed column have been reported [24], but application to detect oil adulteration was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of TOHs was optimized using two miniaturized techniques, namely capillary electrochromatography (CEC) [17][18][19][20] and nano-liquid chromatography (nano-LC) [21]. CEC is a hybrid technique combining aspects of both HPLC and CE.…”
Section: Introductionmentioning
confidence: 99%
“…This method was applied for the qualitative analysis of vitamin E in human serum extracts. Henry et al [102] investigated several RP-stationary phases for the separation of tocopherol a-, b-, g-, and d-isomers. Using a C 30 monolithic stationary phase, the effect of the eluent composition was systematically studied.…”
Section: Vitamins and Food Componentsmentioning
confidence: 99%
“…Effect of the addition of 1% water to the methanol mobile phase on the separation between b-, g-tocopherol isomers using a C 30 monolithic stationary phase. Reprinted from [102], with permission.…”
Section: Vitamins and Food Componentsmentioning
confidence: 99%